Assessment of Gender Equity in the Secondary Social Studies Curriculum: Basis for a Proposed Guide in Preparing Gender Fair Instructional Materials - Tantengco, Nerissa S (ATIKAN, 2013)
ABSTRACT: The study assessed gender equity in the secondary Social Studies curriculum that served as a basis for a proposed guide in preparing gender fair instructional materials. A descriptive analysis of Secondary Social Studies curriculum was the primary method used in this study. The participantsâ perceptions on gender were compared and analyzed. Gender-fair education indicators served as criteria for comparison. The data gathered were processed qualitatively and quantitatively. The findings revealed that: (1) Indicators of gender biases in the learning environment were manifested in the learning environment, curriculum, and instructional processes; (2) Hidden curriculum plays an important role in informally transmitting values and attitudes in schools; (3) Leadership skill and tasks formerly given to male students were checked at present by female assertiveness; (4) Private and public school teachers and students differed in their perceptions on the learning environment; and (5) Gender-fair curriculum in Social Studies is a vital instrument in achieving equality, development, and peace.KEY WORD: Gender equity assessment, Social Studies curriculum, secondary school, gender-fair education, and learning environment.IKHTISAR: Penelitian ini berjudul âPenilaian Kesetaraan Gender dalam Kurikulum Ilmu Pengetahuan Sosial di Sekolah Menengah: Dasar untuk Panduan Pengusulan bagi Mempersiapkan Bahan Ajar Gender yang Adilâ. Ianya menilai kesetaraan gender dalam kurikulum Ilmu Pengetahuan Sosial di sekolah menengah yang berfungsi sebagai dasar panduan yang diusulkan dalam mempersiapkan bahan ajar gender yang adil. Analisis deskriptif terhadap kurikulum Ilmu Pengetahuan Sosial sekolah menengah adalah metode utama yang digunakan dalam penelitian ini. Persepsi peserta tentang gender dibandingkan dan dianalisis. Indikator pendidikan gender yang adil menjadi kriteria untuk diperbandingkan. Data yang dikumpulkan diolah secara kualitatif dan kuantitatif. Temuan menunjukkan bahwa: (1) Indikator bias gender dalam lingkungan belajar dimanifestasikan dalam lingkungan pembelajaran, kurikulum, dan proses pembelajaran; (2) Kurikulum tersembunyi memainkan peran penting dalam transmisi nilai-nilai dan sikap di sekolah secara informal; (3) Keterampilan kepemimpinan dan tugas yang sebelumnya diberikan kepada siswa laki-laki dikaji ulang saat ini oleh ketegasan sikap perempuan; (4) Guru sekolah swasta dan negeri serta para siswa berbeda dalam persepsi mereka terhadap lingkungan pembelajaran; dan (5) Gender yang adil dalam kurikulum Ilmu Pengetahuan Sosial merupakan instrumen penting dalam mencapai kesetaraan, pembangunan, dan perdamaian.KATA KUNCI: Penilaian kesetaraan gender, kurikulum Ilmu Pengetahuan Sosial, sekolah menengah, pendidikan gender yang adil, dan lingkungan pembelajaran.About the Author: Nerissa S. Tantengco, Ph.D. is a Lecturer and Head of the Department of Social Science, College of Arts and Social Sciences PNU (Philippine Normal University), Taft Avenue, Manila, Philippines. For academic purposes, she can be contacted via e-mail at: nstantengco@yahoo.comHow to cite this article? Tantengco, Nerissa S. (2013). âAssessment of Gender Equity in the Secondary Social Studies Curriculum: Basis for a Proposed Guide in Preparing Gender Fair Instructional Materialsâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.3(1) Juni, pp.73-82. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (April 19, 2013); Revised (May 25, 2013); and Published (June 15, 2013).